Exploring the pharmacokinetics, drug-likeness, and toxicological features of anticancer flavonoids: a Boulevard to explore their clinical translational potential - Dubey, Ankit Kumar; Chandragiri, Siva Sai; Geevarghese, Abin V.; Kapoor, Bhupinder; Gulati, Monica; Rani, Pooja; Singh, Gursharan; Chavda, Vivek P.; Gundamaraju, Rohit; Bansal, Himangini; Gautam, Rupesh K.; Goyal, Rajat; et al. (Frontiers in Pharmacology, 2025)
BackgroundFlavonoids that are widely distributed across various plant species exhibit significant anticancer activity in various preclinical and clinical studies, thus offering promising therapeutic prospects. However, a thorough understanding of their pharmacokinetic properties, drug-likeness characteristics, and safety profile is essential for the translational applicability of these molecules into clinical settings.MethodsA systematic search was carried out using various electronic databases such as PubMed Central, ScienceDirect, Clinical Registry, and Google Scholar, using different keywords like “flavonoids”, “cancer”, “pharmacokinetics”, “toxicity”, “tumor”, and their combinations. Non-English literature was excluded due to language barriers, limited accessibility, non-indexing, and the risk of misinterpreting methods or results, which could compromise the accuracy and reliability of the review.Results and discussionThis review provides an in-depth overview of various mechanistic pathways, such as oxidative stress-mediated and immunomodulatory pathways, that are considered to be responsible for the anti-cancer potential of flavonoids. In addition, the pharmacokinetic properties and toxicity profile of flavonoids have been discussed, which are the crucial factors in their clinical translation. Lastly, the review briefly explores various strategies that can be adopted to improve the effectiveness of flavonoids in the treatment of cancer.ConclusionThis investigation enhances our understanding of the translational potential of flavonoid-based therapies by highlighting these essential elements, bringing us one step closer to the development of effective and safe cancer treatments.